APPENDIX TO THE MEASURING OF ENDURANCE OF CADETS IN HANDBALL - Dr Dragan Martinović; Dragan Branković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
At the sample of 80 handball cadet contestants aged between 16-17, there has been done an endurance testing in the discipline of running on a track of total of 12 and 6 minutes. The endurance was estimated in meters of the distance run. The aim of this task was to determine coorelation of the results in running on 12 and 6 minutes. The outcome is a total coorelation between the two. Running of the du- ration of 6 minutes is recommended for the trainer`s practice. Testing is more rational. With the application of the regressive analyses it has been determined that there is depenndance between running time and variables: weight, height and BMI